Associations among risk perception, health efficacy, and health behaviors for cardiovascular disease: an application of risk perception attitude framework - Guo, Zhiting; Chen, Yun; Zhang, Yuping; Ding, Chuanqi; Li, Mei; Xu, Linyan; Jin, Jingfen (Frontiers in Cardiovascular Medicine, 2023)
Background There is currently a pervasive prevalence of cardiovascular disease (CVD) risk worldwide and an inadequate amount of action being taken to promote healthy lifestyle habits. The risk perception attitude (RPA) framework, which classifies individuals based on their risk perception and efficacy belief, enables us to predict their preventive behaviors. We applied the RPA framework to analyze the CVD prevention behaviors among Chinese adults and extended its application to CVD objective risk.Methods A cross-sectional survey was performed in two sites of Zhejiang Province, from March to August 2022, which contained self-reported CVD risk perception, objective CVD risk, efficacy belief, physical activity, healthy diet, and covariates. We used the RPA framework to categorize participants into four groups, then analysis was conducted to estimated inter-group differences in healthy behaviors. We further conducted a hierarchical logistic regression analysis with individuals' health behaviors as the dependent variable, using three blocks of independent variables. Results Among 739 participants, healthy physical activity and healthy diet had significant differences among four RPA groups, post hoc tests clarified that the proportion of respondents with healthy PA in the responsive group (61.6%) was significantly higher than that in other three groups.Risk perception and efficacy belief significantly predicted health behavior against CVD; the relationship between absolute CVD risk and health behavior was moderated by efficacy belief.Early CVD risk screening is crucial, but tailored support and proper understanding of personal risk is essential to promote healthy behaviors. Developing communication and behavioral counseling intervention strategies on the basis of RPA framework has the potential to promote healthy behaviors for CVD prevention.